2010
DOI: 10.1111/j.1365-3016.2010.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Season of birth and diagnosis for childhood cancer in Northern England, 1968–2005

Abstract: The aim of this study was to investigate seasonal variation in the incidence of cancer in children aged 0-14 years. Details of 2959 primary malignant cases (1659 males, 1300 females), diagnosed during the period 1968-2005, were extracted from a specialist registry (the Northern Region Young Persons' Malignant Disease Registry). Seasonal variation was analysed with respect to month of birth and diagnosis. The chi-squared heterogeneity test was used to test for non-uniform variation. Poisson regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 49 publications
7
49
0
Order By: Relevance
“…An interaction between sex and season of birth in relation to AML risk has been reported previously (11). We evaluated for interaction between sex and season of birth by examining sex-stratified risk estimates and formally testing for interaction using a likelihood ratio test.…”
Section: Methodssupporting
confidence: 59%
See 1 more Smart Citation
“…An interaction between sex and season of birth in relation to AML risk has been reported previously (11). We evaluated for interaction between sex and season of birth by examining sex-stratified risk estimates and formally testing for interaction using a likelihood ratio test.…”
Section: Methodssupporting
confidence: 59%
“…Infectious etiologies have been hypothesized for both ALL and AML (9) because of the high incidence of these cancers in early childhood, coinciding with common early infections and immune system immaturity (10). This hypothesis has been supported for ALL by some (1115) but not all (16–18) studies reporting associations with season of birth, a proxy for perinatal infectious exposures. However, season of birth has rarely been studied in relation to AML risk, and has never been examined in large population-based cohort studies with the potential to provide more robust and generalizable risk estimates.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by several previous studies of childhood ALL [3, 6]. The evidence of a possible infectious aetiology for childhood tumours is most established for childhood leukaemia and lymphoma [2, 712], but is also emerging for central nervous system (CNS) tumours [1317] although inconsistencies in the research exist for the latter group [1820]. Despite increasing evidence of an infectious aetiology for childhood tumours, little aetiological research has been undertaken for major cancers occurring in teenagers and young adults (TYA).…”
Section: Introductionsupporting
confidence: 76%
“…Interestingly, most of these findings are in higher latitude countries where seasonal differences in zeitgeber strength are more pronounced. In contrast, no season of birth association was observed for NHL, HD, brain neoplasms, leukaemia, or lymphoma in the UK, Denmark, Sweden, the Netherlands, USA, Belgium, and Canada (Basta et al, 2010;Choi et al, 1977;Crump et al, 2014;Feltbower et al, 2001;Higgins et al, 2001;Hoffman et al, 2007;Langagergaard et al, 2003;Manshande et al, 1985;Meltzer et al, 1996;Schmidt et al, 2009;Van Laar et al, 2013;Van Steensel-Moll et al, 1983).…”
Section: "Photoperiod" At (Season or Seasonality Of) Birth And Associmentioning
confidence: 98%
“…Of seven studies carried out in Denmark, England, USA, and Hungary, all but one (Langagergaard et al, 2003) reported an acute lymphoblastic leukaemia (ALL) clustering for winter birth (with some autumn/spring overlap) (Basta et al, 2010;Feltbower et al, 2001;Halperin et al, 2004;Meltzer et al, 1989;Nyari et al, 2008;Sorensen et al, 2001). Winter birth clustering was also observed for acute myeloid leukaemia (AML) in Sweden (Crump et al, 2015), brain neoplasms combined in Finland and Norway (Heuch et al, 1998;Mainio et al, 2006), glioma in north-east USA (Brenner et al, 2004), and astrocytoma, ependymoma, medulloblastoma, glioblastoma, and germ cell tumours in England, Japan, Denmark, USA, and Germany (Hoffman et al, 2007;Koch et al, 2006;Makino et al, 2011;McNally et al, 2002;Schmidt et al, 2009).…”
Section: "Photoperiod" At (Season or Seasonality Of) Birth And Associmentioning
confidence: 99%